Adults see vision to be more informative than it is. Issue 12 (December 2014) - Wang, J. Jessica; Miletich, Dongo Diana; Ramsey, Richard; Samson, Dana
Humans gain a wide range of knowledge through interacting with the environment. Each aspect of our perceptual experiences offers a unique source of information about the world—colours are seen, sounds heard and textures felt. Understanding how perceptual input provides a basis for knowledge is thus central to understanding one's own and others' epistemic states. Developmental research suggests that 5-year-olds have an immature understanding of knowledge sources and that they overestimate the knowledge to be gained from looking. Without evidence from adults, it is not clear whether the mature reasoning system outgrows this overestimation. The current study is the first to investigate whether an overestimation of the knowledge to be gained from vision occurs in adults. Novel response time paradigms were adapted from developmental studies. In two experiments, participants judged whether an object or feature could be identified by performing a specific action. Adult participants found it disproportionately easy to accept looking as a proposed action when it was informative, and difficult to reject looking when it was not informative. This suggests that adults, like children, overestimate the informativeness of vision. The origin of this overestimation and the implications that the current findings bear on the interpretation of children's overestimation are discussed.